Proyecto sistemas de producción de cuyes - Tomo I - Chauca Francia, Lilia; Zaldivar Abanto, Marco; Muscari Greco, Juan; Higaonna Oshiro, Rosa; Gamarra Montenegro, Julio; Florián Alcántara, Amarante (Instituto Nacional de Investigación Agraria - INIA, 2017)
Instituto Nacional de Investigación Agraria. INIA, Lima-Perú; Centro Internacional de Investigación para el desarrollo. CIID, Canada